Proceso de atención de enfermería en lactante menor con desnutrición crónica. - Vite Sandoya, Kelin Mercedes (2022)
The objective of this case study is based on the nursing care process in minor infant with chronic malnutrition who goes to the emergency area of the Martin Icaza General Hospital when presenting mild edema in the lower limbs, Alteration in thermal rise not quantified 48 hours ago, In addition, the parent states that she is inappetent, His low weight in relation to his age is striking, irritability, flaky dry pale skin, decay, excessive crying, soft spot, dry dull and brittle hair. The chronic malnutrition one of the most common diseases in a minor infant, rom the womb to five years of age. The application of the nursing care process allows us to provide the infant under 2 months of age with the necessary nursing care. It was possible to identify the priority needs based on the functional patterns of Marjory Gordon, a care plan was made in which the Taxonomies were used: NANDA, NIC and NOC.